Upper GI Hemorrhage from Duodenal Ulcer due to Post-Cholecystectomy Clip Migration - Hussain, M Margub; Bhuiya, MA Hashem; Ahmed, Faruque; Masud, MA; Rahman, Atiar; Rahman, Mahfuzur; Kafr, Abdulla-hel; Rahman, Mizanur (Journal of Bangladesh College of Physicians and Surgeons, 2013)
J Bangladesh Coll Phys Surg 2012; 30: 225-228 DOI: http://dx.doi.org/10.3329/jbcps.v30i4.14767